Long-term outcomes of provisional stenting compared with a two-stent strategy for bifurcation lesions: a meta-analysis of randomised trials. Issue 18 (17th March 2017) - Nairooz, Ramez; Saad, Marwan; Elgendy, Islam Y; Mahmoud, Ahmed N; Habash, Fuad; Sardar, Partha; Anderson, David; Shavelle, David M; Abbott, J Dawn
Abstract : Background: The optimal interventional technique for addressing coronary bifurcation lesions is debatable. Long-term clinical outcomes with provisional stenting (PS) compared with a two-stent (TS) strategy for bifurcation lesions are scarce. We aim to perform the first meta-analysis of randomised controlled trials (RCTs) to explore long-term outcomes comparing both strategies. Methods: An electronic search was performed for online databases until August 2016 for RCTs comparing PS with TS for bifurcation lesions reporting outcomes at 1 year of follow-up or more. Random effects model risk ratios (RRs) were calculated for outcomes of interest. Results: Eight RCTs with a total of 2778 patients reported long-term clinical outcomes. At mean follow-up of 3.0±1.6 years, PS was associated with lower risk of all-cause mortality (RR=0.66; 95% CI 0.45 to 0.98; p=0.04) compared with TS for bifurcation lesions. No difference was observed with PS compared with TS regarding major adverse cardiac events (MACE), myocardial infarction (MI), target lesion revascularisation (TLR) or stent thrombosis (ST). In a sensitivity analysis limited to trials with follow-up duration ≥3 years, PS was associated with lower risk of all-cause mortality (RR=0.57; 95% CI 0.36 to 0.88; p=0.01), MACE (RR=0.71; 95% CI 0.52 to 0.97; p=0.03) and MI (RR=0.45; 95% CI 0.21 to 0.96; p=0.04) compared with TS, at mean follow-up of 4.6±0.7 years. The risk of TLR and ST remained similar with both strategies (RR=0.81; 95% CI 0.57 to 1.15; p=0.24; and RR=0.75; 95% CI 0.19 to 2.84; p=0.67 respectively). Meta-regression analyses identified increased risk of MACE with PS in patients presenting with acute coronary syndrome (p=0.05). Conclusion: PS may be associated with a long-term mortality benefit compared with a TS strategy for coronary bifurcation lesions.